Country institutional environments in promoting entrepreneurship: assessment based on developing economies in Asia - Tze Cheng Chew; Tarun Kanti Bose; Yaoyao Fan (Routledge, 2021)
Previous studies have shown that institutional environments play an important role in explaining entrepreneurship in a given country. Yet, most of the extant studies focus on samples derived from developed-economies. While some attentions have been given to countries in developing economies, the focus was mainly on a few rapidly developing countries whereas others remain largely under-explored. Moreover, developing countries in the Asian region provides a compelling context to be studied as it espouses different institutional logics. To address these issues, we assess the perceptions of the regulatory, cognitive, and normative institutional dimensions that may promote entrepreneurship in a sample of 701 business students from three Asian’s developing economies: Malaysia, Bangladesh, and China. In general, the overall institutional environments level for Malaysia and China are perceived as favorable for entrepreneurship whereas Bangladesh is perceived as relatively less favorable for entrepreneurship. Moreover, results suggest that there are significant differences in the country’s institutional environments between Bangladesh and Malaysia, as well as between Bangladesh and China. These results revealed important cross-national differences and invariance between the three countries in the same Asian region. Implications for future research and practice are discussed.